<4 and <8 because they are in the same spot shifted down
Answer: This is what I get.
Step-by-step explanation:
Answer:
B. (3,2)
Step-by-step explanation:
Step 1) When shifting from A(1,2) to B(4,4), the point shifted 3 units to the right (which means x=3) and 2 units upwards (which means y=2).
Step 2) So when you apply the same movements to point C(0,0), the new point will be (3,2).
See the diagram below. Step 1 is the graph on the left. Step 2 is the graph on the right. The movement is colored in green. Hope this helps!
If
![n](https://tex.z-dn.net/?f=n)
is an integer, you can use induction. First show the inequality holds for
![n=1](https://tex.z-dn.net/?f=n%3D1)
. You have
![2^1=2>1](https://tex.z-dn.net/?f=2%5E1%3D2%3E1)
, which is true.
Now assume this holds in general for
![n=k](https://tex.z-dn.net/?f=n%3Dk)
, i.e. that
![2^k>k](https://tex.z-dn.net/?f=2%5Ek%3Ek)
. We want to prove the statement then must hold for
![n=k+1](https://tex.z-dn.net/?f=n%3Dk%2B1)
.
Because
![2^k>k](https://tex.z-dn.net/?f=2%5Ek%3Ek)
, you have
![2^{k+1}=2\times2^k>2k](https://tex.z-dn.net/?f=2%5E%7Bk%2B1%7D%3D2%5Ctimes2%5Ek%3E2k)
and this must be greater than
![k+1](https://tex.z-dn.net/?f=k%2B1)
for the statement to be true, so we require
![2k>k+1](https://tex.z-dn.net/?f=2k%3Ek%2B1)
for
![k>1](https://tex.z-dn.net/?f=k%3E1)
. Well this is obviously true, because solving the inequality gives
![3k>1\implies k>\dfrac13](https://tex.z-dn.net/?f=3k%3E1%5Cimplies%20k%3E%5Cdfrac13)
. So you're done.
If you
![n](https://tex.z-dn.net/?f=n)
is any real number, you can use derivatives to show that
![2^n](https://tex.z-dn.net/?f=2%5En)
increases monotonically and faster than
![n](https://tex.z-dn.net/?f=n)
.
ASSUMING This is a straight line so we gotta the formula for a straight line which is y=mx+b, where m represents the slope and b represents the y intercept.
First, we know this line passes through (5,8) and (9,2) we can use these for finding the equations. When we know two points, we use this formula:
y-y=m(x-x)
The first y is 8 and the second one is 2
The first x is 5 and the second one is 9
Plug it in:
8-2=m(5-9)
6=m(-4)
6/-4=m <— simplify this
m= -3/2
*NOTE: another way to find m is by calculating it (y-y)/(x-x)
Now we know m, we have to find b.
All you gotta do is plug everything you know back into the equation y=mx+b
y=mx+b
y=-3/2x+b <— now plug in a point we know(x,y)
8=-3/2(5)+b
8=-15/2+b
8-(-15/2)=b
b=8+15/2
b=16/2+15/2
b=31/2 (now you can write be as a fraction or a decimal in your equation, depending on what your teacher told you to use)
*NOTE: it is best to use fractions instead of decimals as it is more accurate sometimes.
Now we know all the variables that need to be known, we just need to rewrite the formula of the equation so the teacher can see.
m=-3/2
b=31/2
We don’t need to plug in x or y since it could have different values (since a straight line has MANY co-ordinates)
SO OUR EQUATION IS=
y=(-3/2)x+31/2
Hope you understand this, feel free to ask me anything!